Weingarten tube-like surfaces in Euclidean 3-space - SOROUR, Adel H. (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
In this paper, we study a special kind of tube surfaces, so-called tubelike surface in 3-dimensional Euclidean space E3. It is generated by sweeping a space curve along another central space curve. This study investigates a tubelike surface satisfying some equations in terms of the Gaussian curvature, the mean curvature, the second Gaussian curvature and the second mean curvature. Furthermore, some important theorems are obtained. Finally, an example of tubelike surface is used to demonstrate our theoretical results and graphed. Mathematics Subject Classification (2010): 53A04, 56B34, 53B25.